Automated technology for verification and analysis : 11th International Symposium, ATVA 2013, Hanoi, Vietnam, October 15-18, 2013. Proceedings - Ogawa, Mizuhito; Hung, Dang (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 11th International Symposium on Automated Technology for Verification and Analysis, ATVA 2013, held at Hanoi, Vietnam, in October 2013. The 27 regular papers, 3 short papers and 12 tool papers presented together with 3  invited talks were carefully selected from73 submissions. The papers are organized in topical, sections on analysis and verification of hardware circuits, systems-on-chip and embedded systems, analysis of real-time, hybrid, priced/weighted and probabilistic systems, deductive, algorithmic, compositional, and abstraction/refinement techniques for analysis and verification, analytical techniques for safety, security, and dependability, testing and runtime analysis based on verification technology, analysis and verification of parallel and concurrent hardware/software systems, verification in industrial practice, and applications and case studies.